TEST THE POTENTIAL OF PINEAPPLE (Ananas comosus L.) JUICE TO REDUCE CONTENT OF COPPER (Cu) METAL BY ATOMIC ABSORPTION SPECTROPHOTOMETRY (AAS) - Dinna Fitria; Devina Inggrid Anggraini (Universitas Muhammadiyah Magelang, 2021)
Accumulation of copper (Cu) metal in the body causes tissue damage. Metals that can’t be excreted into the blood or bile by the liver can cause cirrhosis, so the body needs antidotes to reduce metal content. Pineapple (Ananas comosus L.) contains 78% citric acid of total acid. Citric acid was able to form complex compounds with metal. The aims of this research were to know the ability of pineapple juice (Ananas comosus L.) to reduce content of copper (Cu) metal and the concentration of pineapple (Ananas comosus L.) juice that can reduce the highest content of copper (Cu) metal. Pineapple juice was made in five series of concentration (20%, 40%, 60%, 80%, and 100%). Copper metal of 20 ppm was given the addition treatment of each concentration series of pineapple juice. The solution of each concentration was separated using chloroform. The water phase which was the residual copper (Cu) metal that does not react with citric acid, was analyzed using Atomic Absorption Spectrophotometry (AAS) at a wavelength of 324.7 nm. The results of this research were showed that the concentration of pineapple juice 80% can reduce the content of copper (Cu) metal of 24.6896 %.